2016
DOI: 10.1016/j.athoracsur.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Aneurysm

Abstract: Left atrial appendage aneurysms (LAAA) are extremely rare. This condition is usually diagnosed incidentally or after the occurrence of thrombotic events or cardiac tachyarrhythmias in the second to fourth decades of life. It can predispose to hazardous adverse events, including atrial fibrillation, myocardial infarction, and systemic thromboembolism. We report a case of LAAA in a 68-year-old woman presenting with atypical chest pain, exertional dyspnea, and episodes of sudden-onset palpitation. Aneurysmectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…This is probably because of the progressive growth of LAAA with age. Moreover, LAAA has a slight female predominance 2 . Aryal et al proposed a definition of LAAA as a left atrial appendage with an orifice diameter > 2.7 mm, width > 4.8 mm, and length > 6.8 cm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…This is probably because of the progressive growth of LAAA with age. Moreover, LAAA has a slight female predominance 2 . Aryal et al proposed a definition of LAAA as a left atrial appendage with an orifice diameter > 2.7 mm, width > 4.8 mm, and length > 6.8 cm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Left atrial appendage (LAA) is the remnant of embryonic atrium, 1 and ninety percent of clots have been observed in the LAA in patients with non-valvular atrial fibrillation (AF), particularly in cases who has an LAA aneurysmal anomaly. 2 Therefore, we need to evaluate the LAA in AF cases to risk stratify patients regarding the development of cardioembolic events. 3…”
Section: Introductionmentioning
confidence: 99%
“…Researchers argue that the LAA orifice can be obstructed through nominally invasive epicardial or catheter-based transseptal techniques to decrease the risk of stroke. 2,3 Thus, it is necessary to provide precise evidences on the LAA anatomy and dimension before advising the LAA closure devices. One must be aware of the complexity and the variability of shape, size, and number of lobes to avoid misinterpretation and the exact evaluation of LAA closure device.…”
Section: Introductionmentioning
confidence: 99%
“…Left atrial appendage aneurysm is a rare congenital cardiac anomaly with only 132 reported cases from 1962 until 2016. 1,2 This lesion often remains asymptomatic until the third decade of life when patients may present with palpitations, chest pain, dyspnea on exertion, atrial arrhythmias, heart failure, tamponade physiology, or systemic thromboembolism. They also may rarely present with myocardial infarction due to coronary artery compression.…”
Section: Introductionmentioning
confidence: 99%
“…They also may rarely present with myocardial infarction due to coronary artery compression. 2 Surgical resection is recommended due to the persistent risk of these complications with conservative management alone. 1…”
Section: Introductionmentioning
confidence: 99%